KAJIAN TENTANG RASA KHAWATIR PADA KEHIDUPAN “ORANG PERCAYA” DALAM PERSPEKTIF ALKITAB - Renti Sihombing; Eddy Rundjan (STT Bethel The Way, 2019)
The purpose of this study is to analyze what is the cause of concern for human life. Understand and understand the meaning of the concerns experienced by believers and how to overcome them. In addition, it can be useful for readers to be more aware of how to manage their worries in life. The research instrument used in this study is Biblical Study Literature, namely seeking support from Bible verses that discuss concerns. Then it is reviewed theologically. The results of this study conclude that Christ commands that believers do not need to worry about their lives, about what they will eat and drink, and do not need to worry about the future (Matt. 6:25-34). Concern will not solve the problems at hand (Matt. 6:27). In verse 27, the Lord Jesus wants to emphasize that worry is useless. So it can be concluded that the mentality and thoughts of